IWitnessed: Capturing Contemporaneous Accounts to Enhance Witness Evidence. Issue 3 (1st March 2018) - Paterson, Helen M; van Golde, Celine; Devery, Chris; Cowdery, Nicholas; Kemp, Richard
Abstract: Eyewitness testimony can provide critical leads in all types of investigations and can be extremely persuasive in court. However, inconsistencies or inaccuracies in eyewitness accounts can undermine the perceived value of this evidence, leading to miscarriages of justice. Research shows that memory fades quickly after an event. Therefore, it is important for eyewitness accounts to be collected immediately after a critical incident. Unfortunately, it is often unfeasible for police to conduct in-depth interviews at the scene. This has led to the development of immediate recall tools that witnesses can use to record an initial account without the assistance of officers. Until now such recall tools have been limited by their inflexible paper-and-pencil format. To address this issue, a team of researchers in the fields of psychology and law have worked with the New South Wales Police Force to develop iWitnessed, an evidence-based mobile phone application. iWitnessed collects and preserves witness accounts, while providing the witnesses and victims with information about support services. Users can record information as text, images or audio recordings. This application is the first of its kind and represents a novel initiative to improve eyewitness memory evidence.